Clinico-anatomical insight into the unusual course, branching pattern and connections of ulnar nerve: a narrative review - Quratulain Javaid (Journal of the Pakistan Medical Association, 2024)
Ulnar nerve originates from the lower trunk as a branch from anterior division, continuing as a branch from medial cord of the brachial plexus. It receives fibres from anterior rami of cervical nerve root 8 and the first thoracic nerve root. Ulnar nerve injury accounts for being the most common vessel of upper limb that results in hospitalisation. Knowing the variability in the anatomical pattern of ulnar nerve and its communication with various branches of nerves in the vicinity can have implications. The current narrative review comprised literature search on Google, Google Scholar and PubMed databases for articles published between 2015 and 2023 on the subject. The insight and understanding of the related ulnar nerve anatomy is likely to be of prodigious help to anatomists, surgeons, physicians and radiologists in preventing unexpected outcomes in the future. Key Words: Anatomical, Unusual, Course, Branching, Connections, Ulnar nerve.